2013
DOI: 10.1007/s00401-013-1090-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SQSTM1 encoding p62 in amyotrophic lateral sclerosis: genetics and neuropathology

Abstract: Mutations in SQSTM1 encoding the sequestosome 1/p62 protein have recently been identified in familial and sporadic cases of amyotrophic lateral sclerosis (ALS). p62 is a component of the ubiquitin inclusions detected in degenerating neurons in ALS patients. We sequenced SQSTM1 in 90 French patients with familial ALS (FALS) and 74 autopsied ALS cases with sporadic ALS (SALS). We identified, at the heterozygote state, one missense c.1175C>T, p.Pro392Leu (exon 8) in one of our FALS and one substitution in intron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
136
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(154 citation statements)
references
References 47 publications
13
136
1
4
Order By: Relevance
“…7,8 The p.(Pro392Leu) mutation segregates with PDB, and, although the binding of polyubiquitin remains intact, it causes a phenotype that is indistinguishable from those caused by mutations that truncate the entire domain. 27 Third, multiple studies have confirmed the existence of the p.(Pro392Leu) mutation in ALS from different populations, 3,5 and, in combination with the data presented here, it can be concluded that it is the most common mutation in the gene in ALS to date ( Table 1). The coexistence of the p.(Pro392Leu) mutation in a family with a C9ORF72 expansion is not unexpected as C9ORF72 has also been found in FALS cases harbouring SOD1, FUS or TARDBP mutations.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…7,8 The p.(Pro392Leu) mutation segregates with PDB, and, although the binding of polyubiquitin remains intact, it causes a phenotype that is indistinguishable from those caused by mutations that truncate the entire domain. 27 Third, multiple studies have confirmed the existence of the p.(Pro392Leu) mutation in ALS from different populations, 3,5 and, in combination with the data presented here, it can be concluded that it is the most common mutation in the gene in ALS to date ( Table 1). The coexistence of the p.(Pro392Leu) mutation in a family with a C9ORF72 expansion is not unexpected as C9ORF72 has also been found in FALS cases harbouring SOD1, FUS or TARDBP mutations.…”
Section: Discussionsupporting
confidence: 81%
“…important role in the formation of complexes that participate in the NFkB signalling pathway. 26 Second, the coexistence of both PDB and ALS in the two families reported here and in other studies 5 is indicative that common pathogenic mechanisms underlie both these diseases. P62/SQSTM1 has an established causal role in PDB, and the p.(Pro392Leu) mutation is, in fact, the most common cause of PDB.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations